The Influence Of Source, Seed Weight And Scattering Distance On The Growth Of Seaweed ( Kappaphycus Alvarezii) In Mandale Waters Pangkep District, South Sulawesi - Rimal Hamal; Andi Asdar Jaya; Ratnasari Ratnasari; Andi Rusdi Walinono (International Journal of Economics, Business and Innovation Research, 2024)
This research aimed to determine the effect of variety (local and kuljar), seed weight (50 gr, 75 gr, and 100 gr), and stocking distance (20 cm, 25 cm, and 30 cm). This research was carried out in June – August 2023 in the waters of Mandalle. The study used a completely randomized design (CRD) for groups of 3 factors, namely seed weight: 50 gr (P1), 75 gr (P2) and 100 gr (P3), stocking distance: 20 cm (Q1), 25 cm (Q2) and 30 cm ( Q3), seed sources: local seeds (R1) and kuljar (R2). all treatments with 3 (three) replications. The research data were analyzed and continued with the Duncan BNT Test using SPSS 25. Growth measurements were carried out once a week for 35 days. The highest growth in the P3Q1R1 treatment was 3999.7 gr in week V. The results of the analysis of variance obtained the Sig (p) value for the variety variable (<0.05), the Sig (p) value for the seed weight variable (= 0.005) and the Sig value (p-value) stocking distance variable is 0.629 (>0.005). The results of the analysis of variance showed that the interaction between weight and variety had a value of sig (p) (<0.05), the interaction between weight and distance was sig (p) (> 0.05) and the interaction between distance and variety was sig (p) (>0.005). Meanwhile, the interaction of weight, distance and variety is sig (p)(>0.005). The BNT Duncan test results for the P3, Q2R1 weight treatment were the highest, namely 2435.93 gr and were significantly different from other treatments. The lowest P1Q3R2 treatment was 579.37 gr. The results of measuring water quality parameters show high temperature and salinity. To get optimal results, it is recommended to apply a treatment with a seed weight of 100 grams, a scattering distance of 25 cm and use local seeds